Penerapan Economic Value Added (EVA) untuk Mengukur Kinerja Keuangan Apotek Sehat Bersama Parepare - Riska, Riska; Tijjang, Bakhtiar; Sudirman, Irmayanti; Lukman, Siti Diva Syarifah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
The purpose of this study was to determine and analyze financial performance using the EVA method at Apotek Sehat Bersama Parepare to increase economic added value. The data collection techniques used are observation, interviews, documentation and literature study. The analysis method used in this research is quantitative descriptive data. The data analysis method in this study uses the Economic Value Added (EVA) method. The object of this research uses financial statements in the form of statements of financial position (balance sheet) and profit and loss from 2020-2022. The results of the calculation of Economic Value Added (EVA) at Apotek Sehat Bersama Parepare for the period 2020-2022 show that the EVA value for 3 consecutive years produces a positive EVA value, which means that the company has succeeded in increasing economic added value. In 2020 the EVA value was Rp. 102,957,248, - then in 2021 the company's EVA value decreased by Rp. 81,985,229, - and in 2022 the EVA value increased by Rp. 91,236,961, -. It can be seen that the financial performance of Apotek Sehat Bersama Parepare using the Economic Value Added (EVA) method can increase economic added value and the financial performance of Apotek Sehat Bersama Parepare can be said to be good.